PENGUJIAN PENANDA JENIS SPESIFIK PADA JAMUR YANG BERPOTENSI SEBAGAI AGENS PENGENDALI HAYATI PENYAKIT BUSUK AKAR PADA AKASIA - Istiana Prihatini; Anto Rimbawanto; Desy Puspitasari; Dayin Fauzi (Jurnal Pemuliaan Tanaman Hutan, 2018)
Root rot caused by Ganoderma philippii (Bres. & Henn. ex Sacc.) Bres., is an important disease in Acacia plantation. A strategy to control this disease is currently being developed, particularly on the application of biological control agent (BCA). Species specific primers for rapid identification of potential fungi as BCA were developed. This study aimed to obtain the best DNA condition and the best primers for species specific identification. DNA with 20x dilution is the best condition for amplification of the ITS fragment thus used for rapid species identification. The best primer set to detect Cerrena sp. is CrF1/CrR1, PbF2/PbR2 is the best primer set for Phlebiopsis sp. 1. There was no specific primer suitable to detect Phlebia sp. 1 and Phlebia sp. 2 only but Pl-2F1/Pl-2R4 is the best primer set for Phlebia spp.